Case Study Of Pupting Leather Play Sukron Suwondo And His Actions (Sociopragmatic Study): (SOCIOPRAGMATIC STUDY) - Harbono, Harbono (Adpebi International Journal of Multidisciplinary Sciences, 2023)
This research aimed to describe: the peculiarity of Sukron Suwondo leather puppet’s work/performing elements; the Sukron Suwondo’s compliance with story board of Surakarta-style tradition pakeliran in general; types of speech act existing in story Kyai Udan Mas, DåsåmukåLahir, Semar Ngruwat (TTKUMDSLSMG) and determining the dominant speech act, as well as revealing the implicature and pragmatic power in the speech act; types of speech act expressed directly and indirectly, in relation to cooperative/politeness maxim violation in pakeliran Sukron Suwondo. This study was a qualitative descriptive in nature with holistic critique. The findings of research were as follows. Firstly, the performance of Sukron Suwondo’s leather puppet had changed in form, work element, and meaning. Secondly, today Sukron Suwondo appeared as the puppeteer different from others, with his strengths and weaknesses, even some considered him as a controversial and unconventional puppeteer. Thirdly, the out of three stories, the dominant speech act (TTKUMDSLSMG) was as follows. There were 5,085 speech acts. Fourthly, the indirect speech strategy was more frequently used than the direct one. The implication of compliance with cooperative principle maxim was needed when the speaker and the listener emphasized on the cooperative element of speech act.